Postmodernism and the review of history - Pucca, Rafaella Berto (2007)
Abstract The present work aims to make a brief theoretical exposition on the phenomenon widely known as postmodernism, in the sense of showing how this aspect has discussed the revision of history, expanding the spaces of debates in the academies with insertions of voices previously silent in the official discourse (such as those of ethnic and sexual minorities). To this end, we selected some thinkers, such as Linda Hutcheon, Frederic Jameson, Nestor Garcia-Canclini and Irlemar Chiampi, proposing an exhibition that addresses both the first-world discussion about the cultural productions of today, as well as we will present the reflection of some Latin American authors who analyze the phenomenon within our peripheral reality.